2007
DOI: 10.1017/s0018246x06005966
|View full text |Cite
|
Sign up to set email alerts
|

Love and Courtship in Mid-Twentieth-Century England

Abstract: This article contributes to the on-going study of modern affective life by exploring the ways in which love was understood, invoked, and deployed within heterosexual courtships. ‘Love’ itself is approached as a highly mutable and flexible concept whose meanings and uses are contingent upon historical moment, gender, status, and generation. Whilst the article does not claim to offer a comprehensive history of love across the central years of the twentieth century, it suggests that some of the everyday meanings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 2 publications
0
38
0
Order By: Relevance
“…68 Langhamer has also suggested that an emphasis upon greater expectations of marriage may have sown the seeds of later disaffection. 69 In her study The Captive Wife (1966), for example, Hannah Gavron highlighted the dissatisfaction of working-class wives in North London and St Pancras. 70 Up the Junction shows little sense of an ideal of domesticity or companionability.…”
Section: Staring Sultrily: Female Sexuality In Up the Junctionmentioning
confidence: 99%
“…68 Langhamer has also suggested that an emphasis upon greater expectations of marriage may have sown the seeds of later disaffection. 69 In her study The Captive Wife (1966), for example, Hannah Gavron highlighted the dissatisfaction of working-class wives in North London and St Pancras. 70 Up the Junction shows little sense of an ideal of domesticity or companionability.…”
Section: Staring Sultrily: Female Sexuality In Up the Junctionmentioning
confidence: 99%
“…By focusing on personal Dalit women's conversions, I wish to also historicize love and romance, which are mutable concepts (Collin 2003;Langhamer 2007), whose meanings are contingent on gender, caste, and religious identities. Scholars have emphasized shifting meanings of romantic love in colonial India (Orsini 2007, 30-34).…”
Section: Romantic Desires and Conversions To Islammentioning
confidence: 99%
“…Evacuees' foster mothers received a letter from the King and Queen at the end of the war, thanking them for caring for 'children who were in danger'; in so doing they acknowledged the national importance of their domestic labour. 82 Many young women had, as Claire Langhamer suggests, fantasised about romance in wartime and placed increasing emphasis on intimacy; 83 with peace many women attempted to translate their dreams into marriage. Although the post-war housing crisis made establishing a home problematic, as Denise Riley has argued, many young women had what could be seen as a traditional view of the family and longed to give up work on marriage.…”
Section: Longer-term Changesmentioning
confidence: 99%